Kompetencyjny rollercoaster – rodzina, edukacja, praca i (nie)relacyjny wymiar tych przestrzeni - Wawrzonek , Anna (Studia Edukacyjne, 2019)
The main goal of the article is to indicate a significant issue of the shift of roles, competencies and functions we currently notice in various life areas as well as to stimulate reflection on reversing or at least redefining missions of institutions which prepare, or should prepare, for these roles. The insights I want to share are the result of literature studies as well as teaching experiences gained from the academic and school environment. I treat the title competency roller coaster as a metaphor for changes I observe being part of the world of science, education and work.